2012
DOI: 10.1158/1078-0432.ccr-11-2890
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Iniparib to Inhibit Poly(ADP-Ribose) Polymerase In Vitro

Abstract: Purpose Poly(ADP-ribose) polymerase (PARP) inhibitors are undergoing extensive clinical testing for their single-agent activity in homologous recombination- (HR-) deficient tumors and ability to enhance the action of certain DNA damaging agents. Compared to other PARP inhibitors in development, iniparib (4-iodo-3-nitrobenzamide) is notable for its simple structure and the reported ability of its intracellular metabolite 4-iodo-3-nitrosobenzamide to covalently inhibit PARP1 under cell-free conditions. The prese… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
113
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(121 citation statements)
references
References 38 publications
(59 reference statements)
6
113
1
1
Order By: Relevance
“…However, these results could not be reproduced in a phase III trial, raising questions about the future of PARP inhibition as a therapeutic strategy. Remarkably, in striking analogy with tivantinib, subsequent studies showed that iniparib is not a PARP inhibitor but a cytotoxic agent that kills tumor cells by an unrelated molecular mechanism (37,38). In the iniparib as in the tivantinib case, more rigorous preclinical analysis would have addressed these drugs toward a more appropriate clinical testing, preventing failure, and misinterpretation of clinical trials (39).…”
Section: Discussionmentioning
confidence: 99%
“…However, these results could not be reproduced in a phase III trial, raising questions about the future of PARP inhibition as a therapeutic strategy. Remarkably, in striking analogy with tivantinib, subsequent studies showed that iniparib is not a PARP inhibitor but a cytotoxic agent that kills tumor cells by an unrelated molecular mechanism (37,38). In the iniparib as in the tivantinib case, more rigorous preclinical analysis would have addressed these drugs toward a more appropriate clinical testing, preventing failure, and misinterpretation of clinical trials (39).…”
Section: Discussionmentioning
confidence: 99%
“…Poly adenosine-diphosphate [ADP]-ribose polymerases (PARP) inhibitors have also shown their usefulness against cancer cells with defects in DNA repair machinery. In this context and based on the similarities between BRCA1-mutated breast cancers and basal-like phenotype, PARP inhibitors were tested in patients with triple-negative sporadic breast cancers with controversial results 128 . Nevertheless, this supports BRCA1 methylation testing as a good epigenetic marker of response to PARP inhibitors and to other DNA damage drugs, such as platinum-based agents, as well as cisplatin.…”
Section: Clinical and Therapeutic Implications Of Intra-tumor Heterogmentioning
confidence: 99%
“…262 Notably, recent experimental evidence has thrown doubt on the efficacy of Iniparib as a PARP inhibitor. 263 Although PARP may interact with multiple processes involved in DNA damage response 264 and experimental evidence suggested PARP inhibitors may enhance cytotoxic efficacy of different cytotoxic compounds including temozolamide in different models, 265 as for today the jury is still out regarding whether PARP inhibition may have any place in the clinic for tumours wild type for BRCA1/2 except for high-grade ovarian cancers. Immunohistochemical studies have reported reduced 266 as well as elevated 267 PARP expression in triple-negative compared with other types of breast cancers; interestingly, the second study 267 linked elevated PARP levels to improved effect of anthracyclinetaxane combined chemotherapy…”
Section: Homologous Recombination Repairmentioning
confidence: 99%